Enhanced secure interface for a portable e-voting terminal - Zúquete, A. (2015)
This paper presents an enhanced interface for an e-voting client application that partially runs inside a small, portable terminal with reduced interaction capabilities. The interface was enhanced by cooperating with the hosting computer where the terminal is connected to: the hosting computer shows a detailed image of the filled ballot. The displayed image does not convey any personal information, namely the voter's choices, to the hosting computer; voter's choices are solely presented at the terminal. Furthermore, the image contains visual authentication elements that can be validated by the voter using information presented at the terminal. This way, hosting computers are not able to gather voters' choices or to deceive voters, by presenting tampered ballots, without being noticed.